Needs Analysis on Project Base Learning Development to Improve 21st Century Skills - Fauzi, Alfun; Suriswo, Suriswo; Habibi, Beni (Journal of English Language and Education, 2025)
The rapid advancement of the times demands that the world of education prepare students with skills relevant to the 21st century. One approach believed to be effective in addressing this challenge is Project Based Learning (PjBL). This study aims to analyze the needs in developing Project Based Learning (PjBL) to enhance students' 21st-century skills. The method used in this study is the Research and Development (RD) approach, employing the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. In the needs analysis stage, data were collected through observations, interviews, and questionnaires administered to teachers. The analysis results indicate a high need for the development of project-based learning (PjBL); most teachers are aware of the importance of integrating 21st-century skills into learning. The development of Project Based Learning (PjBL) teaching modules is deemed highly necessary. Students' needs also highlight the necessity for a learning approach that is engaging, contextual, and encourages the development of critical thinking, collaboration, communication, and creativity skills.